Body Composition and Resting Metabolic Rate among Team and Individual Games Players at An-Najah National University - Jamal Shaker; Mahmoud Alatrash (My University, 2011)
The purpose of this study was to investigate body composition and resting metabolic rate among team and individual games players at An-Najah National University. The sample of the study consisted of (32) players, and Tanita TBF-410 Bioelectrical impedance analyzer (BIA) was used to determine variables. The result revealed a good level of body composition and resting metabolic rate among team and individual games players at An-Najah National University. Furthermore, the results indicated a significant difference in body mass index and percent of body fat between team and individual games players in favor of team players. Also, the results indicated that there were no significant differences in the other variable between team and individual games players.

هدفت الدراسة التعرف الى مستوى قياسات تركيب الجسم والتمثيل الغذائي خلال الراحة لدى لاعبي فرق الألعاب الجماعية والفردية في جامعة النجاح الوطنية، كذلك التعرف الى الفروق في قياسات تركيب الجسم والتمثيل الغذائي خلال الراحة بين لاعبي فرق الألعاب الفردية والجماعية، ولتحقيق ذلك أجريت الدراسة على عينة قوامها (32) لاعبا، (16) لاعبا من فرق الألعاب الجماعية و(16) لاعبا من فرق الألعاب الفردية. وتم قياس متغيرات الدراسة باستخدام جهاز تانتا (Tanita- TBF- 410) في مختبر القياس الرياضي في كلية التربية الرياضية بجامعة النجاح الوطنية، وأظهرت نتائج الدراسة وجود فروق ذات دلالة إحصائية بين لاعبي الألعاب الجماعية والفردية في متغيري (مؤشر كتلة الجسم ونسبة الشحوم ولصالح فرق الألعاب الجماعية في حين لا يوجد فروق ذات دلالة إحصائية في المتغيرات الاخرى (التمثيل الغذائي خلال الراحة ،وكتلة الشحوم، والكتلة الخالية من الشحوم وكتلة الماء).
تركيب الجسم والتمثيل الغذائي خلال الراحة لدى لاعبي فرق الألعاب الجماعية والفردية في جامعة النجاح الوطنية